Pengaruh Penambahan Daun Jarak dan Jahe Fermentasi dalam Air Minum terhadap Persentase Karkas, Lemak Abdomen, Jantung dan Hati Broiler: Effect of Fermented Jatropha Leaf and Ginger Supplementation in Drinking Water on Carcass, Abdominal Fat, Heart, and Liver Percentage in Broilers - Febrian, Rehanda; Fati, Nelzi; Rahmi, Novadhila (Fakultas Peternakan Universitas Jambi, 2026)
Background: Broilers are a major source of animal protein with rapid growth rates but high susceptibility to diseases, leading to the common use of antibiotics as growth promoters (AGPs) in the poultry industry. However, the ban on AGPs has encouraged the search for safe and effective natural alternatives, one of which is phytobiotics. Purpose: This study aims to evaluate the effect of fermented physic nut (Jatropha curcas Linn.) and ginger (Zingiber officinale var.) leaf in drinking water on carcass percentage, abdominal fat, and physiological organs (heart and liver) of broilers. Method: The study used a Completely Randomized Design (CRD) with five treatments and four replications, involving 100 day-old broiler chicks reared for five weeks. Treatments included the addition of fermented leaf of physic nut and ginger at concentrations of 0%, 0.5%, 1%, 1.5%, and 2%. Results: The results showed that the addition of fermented physic nut and ginger leaf in drinking water had no significant effect (P>0.05) on carcass percentage, abdominal fat, heart, and liver of broilers. Conclusion: The addition of fermented castor leaf and ginger in drinking water had no significant effect (P>0.05) on the carcass percentage, abdominal fat, heart, and liver of broilers. The inclusion of up to 2% fermented castor leaf and ginger in drinking water is tolerable with respect to carcass percentage, abdominal fat, heart, and liver of broilers.